PENERAPAN MATERI KESEHATAN DAN KESELAMATAN KERJA TERHADAP SIKAP DAN PENGUASAAN SISWA DI DAPUR SMK NEGERI 1 POGALAN - Lestariani - Lestariani (STKIP PGRI TULUNGAGUNG, 2022)
This study aims to determine (1) the relationship between students' attitudes towards the implementation of occupational health and safety (K3) in the catering work practice at SMK Negeri 1 Pogalan. (2) The relationship between students' mastery of occupational health and safety materials on the implementation of occupational health and safety (K3) in the public works practice at SMK 1 Pogalan (3) The relationship between student attitudes and student mastery of occupational health and safety material (K3) on the implementation of occupational health and safety (K3) in the public food shop practicum at SMK 1 Pogalan. This research was classified as a correlational descriptive study. The population in this study included all class X JBG1 students, the culinary majors of SMK Negeri 1 Pogalan Trenggalek Regency in the 2015/2016 School Year Odd Semester of 30 people. The results showed: (1) that students who had a positive attitude about K3 were very high at (56%), (2) students who had mastery about K3 material with a very high category of (52.6%), (3) students who have K3 implementation in the workshop with the sang category